Pengaturan Prinsip Hardship pada Kontrak Bisnis dalam Hal Debitur Wanprestasi - Anggraeny Arief; Hambali, Azwad Rachmat (Universitas Islam Negeri Alauddin Makassar, 2023)
This research aims to find out the legality of the principle of difficulty in business contracts in Indonesia and the liability of the debtor if it has defaulted on a business contract related to difficulties. This study used normative legal research. Basically, difficult situations are events that fundamentally change the balance of contract execution due to the COVID-19 pandemic. The responsibility of the Debtor in executing the contract due to non-fulfillment of performance (default) is to remain subject to and follow the rules as stipulated in the Difficulties Provisions Article 6.2.1 and Article 6.2.3 UPICC. The government needs to make regulations regarding the application of the principle of hardship to provide legal certainty and justice for parties whose contract implementation is under difficult conditions or is experiencing difficulties due to the COVID-19 pandemic.